ANALISIS EFISIENSI USAHATANI JAMBU METE (Anacardicum occidentale L) DI DESA TOU KECAMATAN KOTA BARU KABUPATEN ENDE - Fiator Nong; Yovita Yasintha Bolly; Oktaviana Rosario Sere Gili (Fakultas Pertanian, Universitas Nusa Nipa, 2023)
This study was conducted in Tou Village, Kotabaru Sub-district, Ende Regency, in March 2023. The objective of the research was to analyze the revenue, costs, and income obtained by farmers from cashew farming, as well as to assess the profitability and efficiency of the enterprise in Tou Village. The location was deliberately selected because Tou Village is one of the villages actively cultivating cashew. The results indicated that the respondent farmers in Tou Village applied a monoculture planting system, where cashew trees are grown alone on the farmland. Farmers’ income varied, with an average of IDR 4,353,561, the lowest income of IDR 1,133,000, and the highest income of IDR 13,829,500. Economic feasibility analysis showed a benefit-cost ratio (R/C) of 7, indicating that cashew farming in the village is both feasible and profitable to operate.